An Organizational Approach to Understanding How Social Enterprises Address Health Inequities: A Scoping Review. Issue 3 (1st September 2020) - Suchowerska, Roksolana; Barraket, Jo; Qian, Joanne; Mason, Chris; Farmer, Jane; Carey, Gemma; Campbell, Perri; Joyce, Andrew
Abstract: Researchers are turning greater attention to the role of social enterprise in addressing health inequities. However, few studies explicate the organizational features through which social enterprise may improve health equities. This article reports on a scoping study that finds researchers are focusing on understanding the perspectives of target beneficiaries, thus examining the 'transactional' organizational features that are most apparent in daily life—including interpersonal relationships and the allocation of tasks. The role of 'transformational' features—including organizational strategy and leadership—remain relatively unexamined. Given that the transactional and transformational features of organizations are intertwined, future research should develop holistic analyses of organizations that show how social enterprises improve health equities and health equity outcomes.